43 Highly multiplexed digital spatial profiling of the tumor microenvironment of non-small-cell lung cancer (NSCLC). (9th November 2020) - Kulasinghe, Arutha; O'Leary, Connor; Ladwa, Rahul; Warkiani, Majid; O'byrne, Kenneth
Abstract : Background: Profiling the tumour microenvironment (TME) has been informative in understanding the underlying tumour-immune interactions. Multiplex immunohistochemistry(mIHC) coupled with molecular barcoding technologies have revealed greater insights into the TME. Methods: In this study, we utilised the Nanostring GeoMX Digital Spatial Profiler (DSP) platform to profile a NSCLC tissue microarray for protein markers across immune cell profiling, immuno-oncology(IO) drug target, immune activation status, immune cell typing, and pan-tumour protein modules. Regions of interest (ROIs) were selected that described tumour, TME and normal adjacent tissue (NAT) compartments. Results: Our data revealed that paired analysis (n=18) of patient matched compartments indicated that the TME was significantly enriched in CD27, CD3, CD4, CD44, CD45, CD45RO, CD68, CD163, and VISTA relative to tumour. Unmatched analysis indicated that the NAT(n=19) was significantly enriched in CD34, fibronectin, IDO1, LAG3, ARG1 and PTEN when compared to the TM E(n=32). Univariate Cox proportional hazards indicated that the presence of cells expressing CD3 (HR:0.5, p=0.018), CD34(HR:0.53, p=0.004) and ICOS (HR:0.6, p=0.047) in tumour compartments were significantly associated with improved overall survival (OS). Conclusions: We implemented both high-plex and high-throughput methodologies to the discovery of protein biomarkers and molecular phenotypes within biopsy samples and demonstrate the power of such tools for a new generation of pathology research. Acknowledgements: This study was funded by the Princess Alexandra Hospital Foundation grant for KOB. AK is supported by an NHMRC ECF Fellowship (APP1157741) and Cure Cancer (APP1182179). Ethics Approval: The study was approved by the QUT Human Research Ethics Board